Study of CO2 solubility in aqueous blend of potassium carbonate promoted with glycine - Shaikh, M.S. (Trans Tech Publications Ltd, 2014)
CO2 solubility in aqueous potassium carbonate promoted with amino acid (glycine) was measured at temperatures (303.15, 313.15, and 333.15) K over the partial pressure range from 200 to 1000 kPa. The solubility of CO2 is reported as the loading capacity of the CO2 in the solvent, defined as (moles of CO2 per mole of solvent). It was found that the loading capacity of the CO2 increases by increasing the partial pressure of the CO2, whereas, it reduces with increase in temperature. CO2 loading capacity in aqueous potassium carbonate (PC) promoted with glycine (GLY) was also compared with different solvents, which shows that the new solvent blend is considerably better than various solvents. Â© 2014 Trans Tech Publications, Switzerland.